Reduction mammoplasty techniques in post-bariatric patients: our experience - Polotto, Susanna; Grieco, Michele P.; Simonacci, Francesco; Bertozzi, Nicolò; Marchesi, Federico; Grignaffini, Eugenio; Raposio, Edoardo (Acta Biomedica Atenei Parmensis, 2017)
Background and aim of the work: Excessive body weight represents a huge problem affecting a wide part of world population, causing significant physical and psychological consequences. To solve their obesity-related problems, patients should begin a bariatric treatment to lose an adequate percentage of their body mass and therefore, they should be subjected to body contouring surgery. In this article we describe our experience in applying breast remodeling techniques to post-bariatric patients. Methods: We did a retrospective study on our post-bariatric patients subjected to breast reduction and/or mastopexy during a five-years period, considering breast features, kind of surgery performed, aesthetic and psychological outcomes and postoperative complications. Results: Thirty-six post-bariatric patients underwent breast surgery in our unit between 2010 and 2015; their average age was 43 years. The follow up period ranged from 6 months to 4 years and an half. The most frequent surgical techniques performed were Thorek and inferior pedicle breast reduction. The prevalent complications observed were surgical wound delayed healing and nipple-areolar complex (NAC) partial or complete necrosis as immediate ones and unfavorable scarring as delayed ones. Conclusions: Breast reshaping after a massive loss of weight should be forerun by an accurate analysis of breast volume, shape and ptosis degree, in order to obtain optimal results both for the surgeon and the patient.